The impact of transformational leadership on the quality of work-life – An applied study in telecommunications companies -The Hashemite Kingdom of Jordan – - Khasawneh, Maen Yousef (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aims to identify the impact of transformational leadership on the quality of work-life in telecommunications companies operating in the Hashemite Kingdom of Jordan. The researcher has employed the descriptive analytical approach to analyze the study data، the most important results reached in this study are: the overall average answers for the workers on transformational leadership comes high, with an arithmetic average (3.79) , while the quality of work-life has come to a medium degree with an arithmetic average (3.17). The study recommended that leaders in telecommunications companies should be encouraged to continue practicing the transformational leadership style because of its characteristics and practices that have an impact on the effectiveness of the company and taking into account the social and humanitarian aspects of workers.